VÝZNAM STRATEGICKÉHO PLÁNOVANIA V PODMIENKACH ŽELEZNIČNEJ DOPRAVY (Perner's Contacts, 2007)
The article deals with strategic planning and it's signification for assurance of competitive railway system conditions. It deals with historical development of planning, strategic definition and principle steps of strategic planning. This article is a partial outcome of the research grant VEGA n. 1/4171/07 Quality of rail cargo operator processes
Keywords: strategic planning; strategy; railway transport